The now here of global curriculum - Díaz Beltrán, Ana Carolina (Curriculum inquiry, 2018)
In this article, I describe how a curriculum of dislocation produces subjectivities offered in discourses that centre "First World"/Eurocentric/developed subject positions through nation state frameworks. I knit stories of colonialism and imperialism with my lived experiences as a former student in the postcolonial context of Colombia and as a researcher in a new immigrant destination in USA. Using different forms of texts (vignettes, memories, drawings), I offer the reader stories, images, and scenarios to witness the ways in which the privileged spaces of international schools in the "Third World" and public schools in the "First World" are sites in which epistemic violence takes place. These are stories of dislocation, stories of how the embodiment of coloniality happens through the materialization of a Eurocentric modern curriculum of the global. This piece is not only a critique; it tells a story of healing. Based on the work of Chicana feminist Gloria Anzaldúa, I enter a new path to knowledge or "conocimiento" to create a different interpretation of my story. Weaving personal narratives, collective history, theories, and autobiographical vignettes into theoretical prose creates what Anzaldúa calls an/una "autohistoria-teoría."